High seebeck coefficient and power factor in n-type organic thermoelectrics - Zuo, Guangzheng; Li, Zhaojun; Wang, Ergang; Kemerink, Martijn (Advanced electronic materials, 2018)
The n-type thermoelectric properties of [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) are investigated for different solution-based doping methods. A novel inverse-sequential doping method where the semiconductor (PCBM) is deposited on a previously cast dopant 4-(1,3-dimethyl-2,3-dihydro-1H-benzoimidazol-2-yl)-N,N-diphenylaniline film to achieve a very high power factor PF ≈ 35 µW m−1 K−2 with a conductivity σ ≈ 40 S m−1 is introduced. It is also shown that n-type organic semiconductors obey the −1/4 power law relation between Seebeck coefficient S and σ that are previously found for p-type materials. An analytical model on basis of variable range hopping unifies these results. The power law for n-type materials is shifted toward higher conductivities by two orders of magnitude with respect to that of p-type, suggesting strongly that n-type organic semiconductors can eventually become superior to their p-type counterparts. Adding a small fraction lower lowest unoccupied molecular orbital material (core-cyanated naphthalene diimide) into PCBM leads to a higher S for inverse-sequential doping but not for bulk doping due to different morphologies.